2021
DOI: 10.34172/ipp.2022.05
|View full text |Cite
|
Sign up to set email alerts
|

Acute progressive arterial thrombosis after coronary artery bypass graft in a COVID-19 patient

Abstract: The longer the SARS-CoV-2 pandemic takes, the greater the prothrombotic effects of the disease, which varies from venous thromboembolic events to limb arterial thrombosis and stroke. How we deal with the effects of the COVID-19 disease, is still unclear. In this study, researchers will report the clinical presentation, outcome and management of the patient with COVID-19 after coronary artery bypass graft (CABG) surgery, which led to rapid progression of arterial thrombosis. The COVID-19 positive patient underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Based on the evidence, cardiovascular involvement during COVID-19 disease may play a major role in the prognosis. COVID-19 has been associated with increased cardiovascular complications including myocarditis, arrhythmias and pulmonary embolism (2,5).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the evidence, cardiovascular involvement during COVID-19 disease may play a major role in the prognosis. COVID-19 has been associated with increased cardiovascular complications including myocarditis, arrhythmias and pulmonary embolism (2,5).…”
Section: Discussionmentioning
confidence: 99%
“…Intra cardiac thrombosis has rarely been reported in COVID-19 patients (7,8). Right heart thrombus formations a critical condition which can lead to pulmonary embolism (2,9). In some studies, inherited thrombophilia has been reported to increase the risk of thrombosis in COVID-19 patients (10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations